FORMATION OF COLOR CONCEPTS IN CHILDREN'S SPEECH: A PSYCHOLINGUISTIC APPROACH (Ustozlar uchun, 2026)
This article investigates the psycholinguistic processes underlying the formation of color concepts in children's speech, tracing the developmental trajectory from early perceptual discrimination of color to the full acquisition of color lexicon and the culturally mediated conceptual structures associated with it. The article further examines the relationship between color naming errors, overgeneralization, and conceptual restructuring as diagnostic windows into the developing child's cognitive and linguistic system.